Real-World Data on Osimertinib in Chinese Patients with Pretreated, EGFR T790M Mutation Positive, Advanced Non-Small Cell Lung Cancer: A Retrospective Study - Peng D; Shan D; Dai C; Li J; Wang Z; Huang Z; Peng R; Zhao P; Ma X (Cancer Management and Research, 2021)
Da Peng,1 Dongfeng Shan,2 Chengcheng Dai,1 Jie Li,3 Zifan Wang,1 Ziyi Huang,1 Rui Peng,1 Peng Zhao,4 Xuezhen Ma1 1Department of Oncology, Affiliated Qingdao Central Hospital, Qingdao University, Qingdao, Shandong, People’s Republic of China; 2The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 3Department of Oncology, Jiaozhou Central Hospital, Jiaozhou, People’s Republic of China; 4Biotherapy Center, Affiliated Qingdao Central Hospital, Qingdao University, Qingdao, Shandong, People’s Republic of ChinaCorrespondence: Xuezhen MaDepartment of Oncology, Affiliated Qingdao Central Hospital, Qingdao University, No. 127 Siliunan Road, Qingdao, Shandong, 266042, People’s Republic of ChinaTel +86-18660229289Fax +86-532-85953085Email qdlwyxpd@163.comPeng ZhaoBiotherapy Center, Affiliated Qingdao Central Hospital, Qingdao University, Qingdao, Shandong, People’s Republic of ChinaEmail zp8102@126.comPurpose: As a third-generation EGFR TKI has been taken orally, Osimertinib effectively inhibits mutant EGFR, including T790M EGFR resistance mutations. Here, we examined real-world efficacy and tolerability of Osimertinib among Chinese patients with advanced EGFR T790M-mutant NSCLC.Patients and Methods: A total of 106 advanced NSCLC patients who were taking Osimertinib following disease progression after EGFR-TKIs or other treatments were retrospectively recruited in this study. The PFS and OS after Osimertinib treatment were analyzed as the primary endpoints.Results: Osimertinib was used as a second line and ≥ 3rd line treatment in 22.6% and 77.4% of the patients, respectively. DCR and ORR were 93.4% and 57.5%, respectively. Median PFS was 12.4 12 (95% CI, 10.5– 13.5) months. The PFS was 11 (8.0, 14.0) and 12 (10.3,13.7) months (p = 0.373), in patients with and without CNS metastasis, respectively. PFS in 2nd and ≥ 3rd line treatment was 11 (9.0, 13.0) and 12.4 12 (8.9, 15.1) months (p = 0.799), respectively. In patients with EGFR exon 19 deletion and exon 21 L858 mutation, the median PFS was 11 (9.2, 12.8) and 12 (9.2, 14.8) months, respectively (p = 0.833). Median PFS in the monotherapy group and combined anti-angiogenesis group was 11 (9.9,12.1) and 14 (11.2,16.8) months, respectively. Median OS after Osimertinib initiation was 27 (19.6, 34.4) months: 15 (6.9, 23.1) and 27 (22, 32) months in patients with and without CNS metastasis (p=0.027), 27 (20.3,33.7) months and (undefined) as second line or ≥ 3rd line of treatment (p = 0.421), respectively. In patients with exon 19 deletion, the median OS was not reached, and in patients with exon 21 L858 mutations, the median OS was 23 (19.1,29.9) months (p=0.027). Median OS in the monotherapy group was 27 (21.7,32.3) months, and in combined anti-angiogenesis group was not reached (p=0.68).Conclusion: Osimertinib can effectively treat advanced NSCLC with T790M mutations independently of previous treatment lines.Keywords: osimertinib, EGFR-activating mutations, T790M EGFR mutation, tyrosine-kinase inhibitors, non-small cell lung cancer